New Nationwide Common Entrance Examinations to Federal and State Government Colleges on English Lang - Ugo, Ugo C (Ugo c Ugo Publishing Campany Limited, 2002)
This book can be considered as your friend as well as the teacher at home.Pupils preparing to sit for the Common Entrance Examination on English Language can not only practice but can also safely practice them safely at home.
Keywords: Education- English Language